Визначення оптимального розташування мікрофону у акустичному експерименті з використанням м-послідовностей - Огірняк, В. А. (ХНУРЕ, 2019)
For measurements and the search for an optimal location of the microphone with the target to eliminate the disturbance, using auxiliary signals are modeled using M-sequences. Also M-sequences are used indoors as an alternative to a anechoic chamber. The paper presents the experimental results necessary for the development of methods noise measurements using M-sequences.